Dynamic instabilities as mechanisms for emergence - Schöner, Gregor; Dineva, Evelina (Developmental science, 2007)
That competences may emerge given appropriate environmental and behavioral context is a long‐standing theme in developmental research. Work in the motor domain, but also in cognitive development, has made it possible to transform this idea into a mechanistic account closely linked to empirical evidence. In dynamic systems thinking, such capacities as keeping a motor goal in mind, remembering a location, or resisting a motor habit, are all understood in terms of the generation of stable patterns of neuronal activation. These may be input‐driven, but also be stabilized by interactions within neuronal representations. A key theoretical insight is that whether a particular pattern of activation is stable or not is not determined by any single factor, learning process, or structural parameter. Instead, ongoing activity, recent activation history, current input, all may affect when a particular dynamic regime is reachable. In spite of such broad interdependence, sharp transitions may characterize the onset of a skill in any given context. Dynamic instabilities are the mechanistic basis for this phenomenon and thus form the basis for understanding development in terms of emergence. We exemplify the concepts of instability and emergence around the phenomenon of infant perseverative reaching and discuss implications for identifying key markers of development and their link to neuronal processes.